Keabsahan Pengangkatan Anak Piara Mantan Raja Sebagai Kepala Pemerintah Negeri (Desa) - Firmansyah, Mohamad Z; Bakarbessy, Andress Denny; Pattinasarany, Yohanes (PATTIMURA Law Study Review, 2025)
Article 3 paragraph (2) of the Malteng Regional Regulation No. 1 of 2006 stipulates that "the position of the head of the State government is the right of certain families/descendants based on a straight line and cannot be transferred to other parties except in special matters determined based on the results of the deliberations of the family/descendants who are entitled to the State Saniri. It is reaffirmed in Article 3 paragraph (1) of the Regional Regulation of Central Maluku Regency Number 3 of 2006 concerning Procedures for the Nomination, Election and Inauguration of the Head of State Government stipulates that "The position of the Head of State Government is the right of certain heads of the house/descendants to determine based on the deliberation of the heads of the houses/descendants. This type of research is Empirical Juridical, In this study the approach used in solving the problem is by using the empirical juridical approach method, the data that has been collected is analyzed qualitatively whose decomposition is systematically arranged based on legal disciplines to achieve clarity of the problem to be discussed. The results of this study show that the position of the Head of State Government is the right of the family/descendants of the parentah, as stipulated in the provisions of Article 3 Paragraph (1) of the Malteng Regional Regulation No. 3 of 2006 which stipulates that the position of the Head of State Government is the right of the family/descendants to determine based on the deliberation of the family/descendants. Therefore, the appointment of the former king's son as the head of the government has no validity, for this reason the appointment of Muhammad R. Fahlefi Ely as the Head of the Assilulu State Government has no validity. The appointment of Muhammad Fahlevi Ely as the Head of the Assilulu State Government in an authoritative manner is not in accordance with the mandate of the Central Maluku Regency Regional Regulation No. 1 of 2006 and the Central Maluku Regency Regional Regulation No. 3 of 2006, where Muhammad R. Fahlefi Ely is the Son of the Former King and not based on the descendants of the family in a straight line, therefore due to the law of the appointment of Muhammad Fahlevi Ely as the Head of the Assilulu State Government does not have validity, and is considered null and void, as formulated in Article 70 Paragraph of Law Nomor 30 of 2014.